Mechanical and Enzymatic Procedures to Isolate the Stromal Vascular Fraction From Adipose Tissue: Preliminary Results - Senesi, Letizia; De Francesco, Francesco; Farinelli, Luca; Manzotti, Sandra; Gagliardi, Giulio; Papalia, Giuseppe Francesco; Riccio, Michele; Gigante, Antonio (Frontiers in Cell and Developmental Biology, 2019)
Adipose-derived MSCs (ASCs) and stromal vascular fraction (SVF) play an important role in regenerative medicine and in the treatment of osteoarthritis. ASCs extracted from lipoaspirates are a valuable cell source due to their abundance and accessibility. ASCs are retrieved from the aqueous fraction of the digested lipoaspirate. The aqueous fraction is known as SVF and includes, ASCs, endothelial precursor cells (EPCs), endothelial cells (ECs), macrophages, smooth muscle cells, lymphocytes, pericytes, as well as pre-adipocytes. To date, two types of techniques to isolate SVF have been proposed: enzymatic and mechanical. The enzymatic method is particularly indicated in SVF isolation since it disrupts the extracellular matrix (ECM) and the binding of adipocytes and other cells but is restricted by regulatory issues related to enzymatic procedures, especially within the European Community. Thus, making the search for alternative mechanical methods imperative. This study assesses the SVF harvested from subcutaneous abdominal fat via two different mechanical procedures and the standard enzymatic method to evaluate their eligibility in a clinical context. In particular, we analyze cell viability (at 0 and after 72 h) as well as the expression of cluster differentiation (CD) for each sample and the differentiation in adipocytic, chondrocytic, ostheocytic linage. The mechanical procedures yielded no significant difference in cell viability and cluster differentiation pattern expression, even if enzymatic procedure still remain the ‘gold standard’. We retain that clinical efficacy in treating ostheoarthrosis with SVF administration is probably related to his anti-inflammatory and immunoregulatory effect, rather than the ability to differentiate in specific cell lineage. However, further studies are required to support and improve our findings.